2020
DOI: 10.3928/01477447-20191031-01
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of Intraoperative Arthrogram in the Management of Pediatric Lateral Condyle Fractures of the Humerus

Abstract: Intraoperative arthrograms are commonly used in conjunction with closed reduction and percutaneous pinning (CRPP) of pediatric lateral condyle fractures of the humerus. The authors sought to determine how arthrograms affect management of these fractures. They reviewed all lateral condyle fractures treated surgically at a pediatric level I trauma center from 2008 to 2014. They stratified patients managed with and without an arthrogram as well as by timing of arthrogram. The authors compared injury parameters, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…The expansion of non-operative treatment to LCFs with 2 to 4 mm displacement based on preoperative US would probably reduce the incidence of complications seen with CRPP and ORIF and result in quicker recovery of elbow function as it has been reported with nonoperative treatment [10]. [2] findings also indicate that all of Weiss et al's [9] 65 type II LCFs and possible the majority of Swarup et al's [1] 47 LCFs could potentially have been treated successfully without surgery.…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…The expansion of non-operative treatment to LCFs with 2 to 4 mm displacement based on preoperative US would probably reduce the incidence of complications seen with CRPP and ORIF and result in quicker recovery of elbow function as it has been reported with nonoperative treatment [10]. [2] findings also indicate that all of Weiss et al's [9] 65 type II LCFs and possible the majority of Swarup et al's [1] 47 LCFs could potentially have been treated successfully without surgery.…”
mentioning
confidence: 74%
“…The authors stated that it is common practice to perform an arthrogram after closed reduction and percutaneous pinning (CRPP) of minimally displaced lateral condyle fractures (LCFs) but in contrary to the former, we could only identify five other articles in the literature which documented the use of an arthrogram after CRPP [2][3][4][5][6]. Two of the former authors [2,3] stated that the arthrogram did not change the treatment decision, two [4,5] did not provide this information and Xie et al [6] reported a conversion of CRPP to open reduction and K-wire fixation (ORIF) in 10 of 46 patients. Kang et al [7] converted nine of 39 CRPPs to ORIF after arthroscopic assessment.…”
mentioning
confidence: 99%
“…At present, the preferred examination method is still elbow joint frontal and lateral radiograph, but it does not always accurately diagnose HLCFs, nor can it provide enough information to judge fracture stability to determine the best treatment and prevent secondary fracture displacement [ 8 10 ]. Therefore, many other diagnostic methods (such as transverse ultrasonography, arthroscopy, and arthrogram) have been recommended as additional tests to evaluate and diagnose HLCFs in children [ 11 13 ]. However, these examinations are invasive and can’t be used routinely for reasons such as the high cost, needing patient sedation, or the poor reproducibility of results.…”
Section: Discussionmentioning
confidence: 99%
“…In the HTa group, the arthrogram was performed as previously described (0.5 ml -1.0 ml, Iodixanol, GE Healthcare, Ireland) [ 11 13 ]. The process of reduction and pinning was consistent with the Baumann group, except for the utilization of HTa in the assessment of reduction.…”
Section: Methodsmentioning
confidence: 99%
“…An arthrogram is initially developed as a novel technique to assess the cartilage injury of joints when CT or MRI is not available, which is designed to make the articular surface visible under fluoroscopy by the injection of an appropriate contrast agent into the joint [ 11 ]. With the advantage of minimal invasion, arthrogram has been successfully employed in series of investigations, such as radial head fractures and lateral condylar fractures in children [ 12 – 14 ].…”
Section: Introductionmentioning
confidence: 99%